2001
DOI: 10.1097/00005131-200111000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Plate Fixation of Olecranon Fractures

Abstract: Plate fixation is an effective treatment option for displaced olecranon fractures with a good functional outcome and a low incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
116
1
20

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(142 citation statements)
references
References 20 publications
5
116
1
20
Order By: Relevance
“…These findings are different from those described in other studies, in which the authors conclude that the quality of life of patients is preserved, when compared to the general population. 13,[16][17][18] In this study, this comparison proved impossible as there are no data on quality of life of the Brazilian population analyzed by SF-36. Statistically significant correlations between the physical aspect, vitality and social aspect domains of SF-36 and DASH were found.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These findings are different from those described in other studies, in which the authors conclude that the quality of life of patients is preserved, when compared to the general population. 13,[16][17][18] In this study, this comparison proved impossible as there are no data on quality of life of the Brazilian population analyzed by SF-36. Statistically significant correlations between the physical aspect, vitality and social aspect domains of SF-36 and DASH were found.…”
Section: Discussionmentioning
confidence: 94%
“…In other words, the lower the patient's age bracket, the lesser the extent of limitations related to physical capacity, the better the general state of health and the higher the levels of energy and vigor. 13,16 In relation to gender, significant statistical correlation was observed with the functional capacity and vitality domains of SF-36. Unlike the study found in literature, the male patients presented results that were superior to those of the female patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…O tratamento padrão para as FLEPA consiste em redução aberta e fixação interna estável da fratura, que permita mobilização precoce e rápida recuperação funcional (3,(9)(10)(13)(14) . Em nossos pacientes, a fratura foi reduzida por via posterior, que permite acesso global ao cotovelo, e fixada com placa de compressão dinâmica (DCP) aplicada à crista da ulna, exceto em um caso (caso 30), cuja fratura epifisária do olécrano foi fixada com banda de tensão.…”
Section: Sexo E Resultadosunclassified
“…Todas essas complicações são amplamente relatadas na literatura científica (2,(9)(10)13,21) e refletem a gravidade e dificuldade no tratamento das fraturas complexas da região proximal do antebraço.…”
Section: Discussionunclassified